Effects of different doses of fertilizers on growth and yield components of biodiesel plant (Jatropha curcas L.) - Shah, Inam Ali; Wazir, Sultan Memod; Khan, Rahmat Ali (Penerbit Universiti Kebangsaan Malaysia, 2017)
Effects of different doses of fertilizers on growth and yield components of biodiesel plant (Jatropha curcas L.), was made in the prevailing environment of University of Science and Technology Bannu. The experiment was carried out in randomized complete block design (RCBD) with three replications. Nitrogen, phosphorus and potassium were applied in the form of urea, single super phosphate and potash in the shape of combined NPK, respectively, during sprouting of leaves and thereafter with each irrigation in split doses. The analysis of variance for number of branches per plant showed significant results indicated in ANOVA. Significantly the number of primary branches per plant 8.07 was recorded in T4 with the application of dose of (N P K: 2507.5 gm: 1091.5 gm: 501.5 gm). Maximum No. of secondary branches per plant (9.100) were recorded in T1 especially at both plots. Flower per inflorescence showed that maximum value (122.810) was recorded in T5 of especially at both plots. Inflorescence plant-1 showed that maximum value (39.477) were recorded in T1 and minimum value were noted as (12.733) at T3 on both the flats. The data for fruits per plant showed that maximum value (143.300) was recorded in T1. The seed index, which was the output of the aim of this research work, reflects highly significant differences in mean value observed for both subplots. Mean values showed that maximum seeds weight 45.86 was recorded in T1 of especially at both plots while low seed index was noted as 22.84 at T5 (N: 3400 gm, P: 1480 gm, K: 680 gm) at both the subplots.